2018
DOI: 10.3390/ma11122505
|View full text |Cite
|
Sign up to set email alerts
|

CVD Diamond Interaction with Fe at Elevated Temperatures

Abstract: Chemical vapor deposition (CVD) diamond is a prospective thin film material for cutting tools applications due to the extreme combination of hardness, chemical inertness, and thermal conductivity. However, the CVD diamond cutting ability of ferrous materials is strongly limited due to its extreme affinity to iron, cobalt, or nickel. The diamond–iron interaction and the diffusion behavior in this system are not well studied and are believed to be similar to the graphite–iron mechanism. In this article, we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…On one hand, nickel nanoparticles transform the diamond into non-diamond carbon, and gradually penetrate into the diamond film grains by absorbing graphite atoms. 31,32 On the other hand, the concentration of non-diamond carbon is higher in the process of contact between nickel nanoparticles and diamond film. During microwave plasma etching, diamond carbon is etched and diffuses into nickel to form graphite and non-diamond carbon.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, nickel nanoparticles transform the diamond into non-diamond carbon, and gradually penetrate into the diamond film grains by absorbing graphite atoms. 31,32 On the other hand, the concentration of non-diamond carbon is higher in the process of contact between nickel nanoparticles and diamond film. During microwave plasma etching, diamond carbon is etched and diffuses into nickel to form graphite and non-diamond carbon.…”
Section: Resultsmentioning
confidence: 99%
“…The diamond cutting ability of ferrous materials is strongly limited due to its extreme affinity to iron; diffusion of Fe is reported into the diamond layer at higher temperatures (from 600 °C) [Zenkin et al (2018)]. In DSC (differential scanning calorimetry) curves, they observed inflection points about 890 °C corresponding to the transition temperature of the diamond graphitization reaction Lee et al, 2019.…”
Section: Computational Resultsmentioning
confidence: 99%
“…In practical applications, such as diamond tools, diamond drill bits, and high flux heat sinks, diamond will inevitably contact ferrous materials, and reactions happen at the interfaces; thus understanding the underlying mechanism is crucial to altering the interfacial binding, connections, and device performance 11‐14 . Taking diamond and iron (Fe) interface as an example, it is reported that the interfacial reaction consists of two steps, that is, graphitization of diamond and subsequent diffusion of carbon atoms into Fe 15‐21 . The unpaired d ‐electrons of Fe interact with the sp 3 ‐hybridized electrons in carbon and shift the positions of carbon atoms, resulting in the transformation of diamond into graphite at the diamond–Fe interface at high temperature 18,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Taking diamond and iron (Fe) interface as an example, it is reported that the interfacial reaction consists of two steps, that is, graphitization of diamond and subsequent diffusion of carbon atoms into Fe. [15][16][17][18][19][20][21] The unpaired d-electrons of Fe interact with the sp 3 -hybridized electrons in carbon and shift the positions of carbon atoms, resulting in the transformation of diamond into graphite at the diamond-Fe interface at high temperature. 18,22,23 However, nongraphitization was also proposed for diamond-Fe reaction with the aid of molecular dynamic simulations.…”
mentioning
confidence: 99%